EFFECTS OF FORWARD SPEEDS AND BLADE ANGLES OF POTATO DIGGER ON FUEL CONSUMPTION AND TUBER MECHANICAL DAMAGES - Zhyar Abdulla; Arkan Sedeeq; Fawzi Khorshid (Mesopotamia Journal of Agriculture)
This experiment was conducted in Shamamik- Erbil state in Iraq-Kurdistan Region during the middle of summer of 2021 in order to determine the effects of different blade angles and forward speeds of potato digger in the fuel consumption and mechanical damages. Split plot arrangement under Randomized Completely Block Design was replications. Two blade angles (180) and (220) were located as main plot, while three forward speeds 2.6, 3.51 and 4.36 Km.h-1 were located as sub plots. The results were as following: the blade angle of (220) recorded the lowest percentage values for all studied traits, namely, undamaged tubers, severe damage, slight damage, lifted tubers and damage index except in digging depth and fuel consumption which gave higher values than those obtained from the blade angle of (220). By increasing the forward speed, weight of (undamaged tubers 69.11%, lifted tubers 79.27% and digging depth 26.16cm) were decreased, while the rest of the traits increased. At any blade angle (180 , 220), as the forward speed increased, the values of (severe damage1.84%,2.87%,slight damage17.50%,12.48, fuel consumption 44 , 43 litter.ha-1 and damage index 142 , 104) were increased, while the other attributes decreased